2014
DOI: 10.1002/bio.2645
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence enhancement monitoring of pyrromethene laser dyes by metallic Ag nanoparticles

Abstract: Fluorescence enhancement monitoring of pyrromethene laser dyes using their complexation with Ag nanoparticles (Ag NPs) was studied. The size of the prepared Ag NPs was determined by transmission electron spectroscopy and UV/Vis absorption spectroscopy. Mie theory was also used to confirm the size of NPs theoretically. The effect of different nanoparticle concentrations on the optical properties of 1 × 10(-4) M PM dyes shows that 40%of Ag NPs concentration (40%C Ag NPs) in complex is the optimum concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…Hence, the interest in studying FRET in the presence of NPs has increased, and several studies have reported the usage of ZnO NPs as an energy donor or to control the energy transfer process [14]. It has been shown that the spectral overlap integral, the orientation of transition dipole moment of the donor and acceptor, fluorescence lifetime, size and shape of the NPs, radiative decay rate, and quantum yield of the donor molecule affect the strength of FRET [35,52].…”
Section: Fret Ability Of Phytosynthesized Zno Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the interest in studying FRET in the presence of NPs has increased, and several studies have reported the usage of ZnO NPs as an energy donor or to control the energy transfer process [14]. It has been shown that the spectral overlap integral, the orientation of transition dipole moment of the donor and acceptor, fluorescence lifetime, size and shape of the NPs, radiative decay rate, and quantum yield of the donor molecule affect the strength of FRET [35,52].…”
Section: Fret Ability Of Phytosynthesized Zno Npsmentioning
confidence: 99%
“…Fluorescence enhancement near the NPs' surfaces occurred due to interaction with SPR, a decrease in non-radiative decay, an increase in photostability of the dye, and the change in local dielectric properties of the medium [14,35,52]. Thus, to observe a sufficient fluorescence enhancement, the dye molecules should be located at a greater distance (>10 nm) from the metal surface [52]. Moreover, the size and morphology alter the energy band gap of the NPs, which in turn affect the spectral characteristics and FRET efficiency [4].…”
Section: Fret Ability Of Phytosynthesized Zno Npsmentioning
confidence: 99%
“…The peak around 600 nm was the characteristic absorption of D5-Ag NC (Fig. S3a), while the peak at about 400 nm was the absorption of Ag nanoparticles (Ag NPs), (Kundu, 2013;Molotsky et al, 2010;Sakr et al, 2014;Sinha et al, 2014), the small amount of Ag NPs in the system had been proved to have little impact on the fluorescence behavior of DNAAg NCs (Guo et al, 2010;Ma et al, 2011;Zhang et al, 2013aZhang et al, , 2013bZhang and Ye, 2011). High resolution transmission electron microscopy (TEM) was further used to characterize the morphology of D5-Ag NCs, Fig.…”
Section: Optimization and Characterization Of Dna-ag Ncsmentioning
confidence: 98%
“…Moreover, ZnO NPs are being applied as bright fluorescent markers with enhanced photostability in fluorescence microscopy, sensor technology, and microarrays due to the interaction of fluorophores with MONPs, displaying various spectral changes such as enhancement in luminescence intensity, photostability, and quantum yield [33][34][35]. Fluorescence resonance energy transfer (FRET), a non-radiative quantum mechanical process that relies on the distance and energy transfer from an excited state donor to a ground state acceptor through dipole-dipole interactions [33,[35][36][37], is being widely used in polymer science, biochemistry, and structural biology [15,35]. The energy transfer between quantum dots has been investigated broadly to design FRET sensors [38][39][40].…”
Section: Of 21mentioning
confidence: 99%
“…To the best of our experience, the present study remains the first endeavor that used biogenic ZnO NPs synthesized from Heliotropium indicum (H. indicum) to investigate the efficacy of FRET. In FRET, when NPs are in close proximity to fluorophores, quenching of the luminescence occurs because the non-radiative decay of the excited molecules will increase due to energy transfer from the dyes to the NPs; conversely, when NPs are located at a greater distance, enhancement of the luminescence is observed due to a decrease in non-radiative decay [15,33,[35][36][37]. These effects have been explained by interactions with surface plasmon resonance in the NPs and fluorophore [15,41].…”
Section: Of 21mentioning
confidence: 99%